Mediation for sustainable peace : the Trilateral Agreement of 1988 between the Republic of South Africa the People's Republic of Angola and the Republic of Cuba for Namibian independence - Schoeman, Maxi (University of Pretoria, 2016)
Mini Dissertation (MA)--University of Pretoria, 2015.